Orthotopic and Heterotopic Murine Models of Pancreatic Cancer Exhibit Different Immunological Microenvironments and Different Responses to Immunotherapy - Wang, Jin; Liu, Xingchen; Ji, Junsong; Luo, Jianhua; Zhao, Yuanyu; Zhou, Xiaonan; Zheng, Jianming; Guo, Meng; Liu, Yanfang (Frontiers in Immunology, 2022)
For decades, tumor-bearing murine models established using tumor cell lines have been the most commonly used models to study human cancers. Even though there are several studies reported that implant sites caused disparities in tumor behaviors, few of them illuminated the positional effect on immunotherapy. Herein, we describe surgical techniques for a novel orthotopic implantation of syngeneic pancreatic ductal adenocarcinoma (PDAC) tissue slices. This method has high success modeling rate and stable growth kinetics, which makes it useful for trialing novel therapeutics. Pathological examination indicated that the orthotopic tumor displayed poor vascularization, desmoplastic stromal reaction, and a highly immunosuppressive tumor microenvironment. This unique microenvironment resulted in limited response to PD1/CTLA4 blockade therapy and anti-MUC1 (αMUC1) CAR-T transfer treatment. To reverse the suppressive tumor microenvironment, we developed gene modified T-cells bearing a chimeric receptor in which activating receptor NKG2D fused to intracellular domains of 4-1BB and CD3ζ (NKG2D CAR). The NKG2D CAR-T cells target myeloid-derived suppressor cells (MDSCs), which overexpress Rae1 (NKG2D ligands) within the TME. Results indicated that NKG2D CAR-T cells eliminated MDSCs and improved antitumor activity of subsequently infused CAR-T cells. Moreover, we generated a bicistronic CAR-T, including αMUC1 CAR and NKG2D CAR separated by a P2A element. Treatment with the dual targeted bicistronic CAR-T cells also resulted in prolonged survival of orthotopic model mice. In summary, this study describes construction of a novel orthotopic PDAC model through implantation of tissue slices, and discusses resistance to immunotherapy from the perspective of PDAC microenvironment. Based on the obtained results, it was evident that elimination MDSCs by NKG2D CAR could rescue the impaired CAR-T cell activity.